'Still living with it even though it's gone': Using interpretive phenomenological analysis to explore shared experiences of living with and beyond breast, prostate, and colorectal cancer. (February 2022) - Le Boutillier, Clair; Urch, Catherine; King, Alex; Barry, Claire; Mansfield, Louise; Archer, Stephanie
Abstract: Purpose: Living with and beyond cancer is an increasingly common experience. While research is uncovering valuable individual experiences of those living with and beyond cancer, it has been argued that this idiographic approach is limited in outlook, reach and impact. This study contributes to the understanding of what it means to live with and beyond cancer by complementing idiographic knowledge with multiple perspectives from a group of participants who are living with and beyond cancer, to explore how individual experiences may be relevant to others. Method: Semi-structured interviews were conducted with people who had received treatment for breast (n = 6), prostate (n = 6) or colorectal cancer (n = 6). Data were analysed using interpretive phenomenological analysis. The early findings were then shared with a wider group of people who had received treatment for breast, prostate or colorectal cancer (n = 26) in six focus groups, to explore whether they had similar experiences. Results: While individual accounts of living with and beyond cancer detail unique features specific to each person's experience, focus group discussions illustrated how participant life worlds interact and overlap. The findings identified thematic similarities within and between individual and group levels and across cancer types. Three super-ordinate themes describe the shared experience of living with and beyond cancer: i) the cancer shock, ii) managing cancer and getting through and iii) getting over cancer. Conclusions: A multiple perspective approach informs our understanding of shared experiences of living with and beyond cancer. This knowledge can be used to direct, design, and deliver relevant supportive cancer care. Highlights: Living with and beyond cancer is an emerging concept in international cancer care and an increasingly common experience. This study contributes to the understanding of what it means to live with and beyond cancer by complementing idiographic knowledge with multiple perspectives. Individual accounts offer the foundation, and shared experiences provide a central overarching scaffold, for developing personalised supportive cancer care. The novel multi-perspective IPA design allows us to move beyond the idiographic to a more comprehensive and detailed view of living with and beyond cancer.